Factors contributing to food insecurity among older persons in Malaysia: Findings from the National Health and Morbidity Survey (NHMS) 2018. (28th December 2020) - Salleh, Ruhaya; Man, Cheong Siew; Ahmad, Mohamad Hasnan; Palaniveloo, Lalitha; Zulkafly, Norlida; Ab.Halim, Siti Adibah; Baharudin@Shaharuddin, Azli; Sulaiman, Norhasmah; Che Abdul Rahim, Norsyamlina; Abdul Aziz, Nur Shahida; Mohd Sallehuddin, Syafinaz; Pardi, Munawara; et al.
Abstract : Aim: Older persons are vulnerable to food insecurity. Therefore, this study aimed to determine the prevalence of food insecurity and associated factors among older persons in Malaysia. Methods: This is a cross‐sectional study with two‐stage stratified random sampling. In total, 3977 older persons participated in this study. Face‐to‐face interviews were conducted using a mobile device to obtain information about socio‐demographic background, food insecurity, non‐communicable diseases, social support and living arrangements. Descriptive and multiple complex sample logistic regression analyses were performed for data analysis. Results: The overall prevalence of food insecurity among older persons was 10.4%. Older persons from rural areas with no or only primary and secondary education, income less than RM 2000 (USD 477.57), at risk of malnutrition and not receiving very high social support were more likely to be food‐insecure. Conclusion: Approximately, one‐tenth of Malaysian older adults were classified as food‐insecure; particularly those living in rural areas from lower socio‐economic status, not receiving very high social support and malnourished were more likely to be at risk. A specific nutrition program, such as meals on wheels and food vouchers, should be targeted toward older persons who are at risk to improve their malnutrition status. Geriatr Gerontol Int 2020; 20: 73–78 .